Silica Gel-Mediated Hydroamination/Semipinacol Rearrangement of 2-Alkylaminophenylprop-1-yn-3-ols: Synthesis of 2-Oxindoles from Alkynes and 1-(2-Aminophenyl) Ketones - Susanti, Dewi (2014)
2-Alkylaminophenylprop-1-yn-3-ols, prepared from the lithium diisopropylamide (LDA)-mediated 1,2-addition of alkynes to 1-(2-aminophenyl) ketones, can be converted to 3,3-disubstituted 2-oxindoles by using silica gel in n-hexane/ethyl acetate (20:1 v/v) as the reaction medium. The utility of the approach as a potential scale-up strategy for the synthesis of 2-oxindoles was exemplified by the large-scale synthesis of one adduct in excellent yield. The synthetic applicability of this chemistry was also demonstrated by the recycling of the silica gel up to 8 times with no apparent loss of activity being observed for the same example.